'Remember Cassinga?' An exhibition of photographs and histories - Williams, Christian A. (Kronos: Southern African Histories, 2017)
Since May 4, 1978, the day it was attacked by the South African Defence Force, Cassinga has been a key site in the national history of Namibia. Within days of the assault, news spread through the exile community and around the world about the attack on SWAPO's refugee camp at Cassinga, which had left at least 600 dead and hundreds more wounded. In the years that followed, Namibians have narrated a history of Cassinga that highlights the brutality of the South African apartheid regime, the bravery of those who resisted it, and the magnanimity of those who reconciled with their former oppressors.